Cascade energy transfer and tunable emission from nanosheet hybrids: locating acceptor molecules through chiral doping (vol 53, pg 7072, 2017) - Goudappagouda; Wakchaure, Vivek Chandrakant; Ranjeesh, Kayaramkodath Chandran; Abhai, Chalona Antony Ralph; Babu, Sukumaran Santhosh (Chemical Communications, 2019)
Correction for `Cascade energy transfer and tunable emission from nanosheet hybrids: locating acceptor molecules through chiral doping' by Goudappagouda et al., Chem. Commun., 2017, 53, 7072-7075.